Soil microbiomes: a promising strategy for boosting crop yield and advancing sustainable agriculture - Komal Pandey; Baljeet Singh Saharan (Discover Agriculture)
Abstract Agricultural intensification, driven by the excessive use of agrochemicals (e.g., fertilizers and pesticides), simplified cropping systems (e.g., monocropping, tillage, and heavy machinery), and exacerbated by climate-related stressors (e.g., drought, salinity, and flooding), has led to profound and long-lasting negative effects on soil health and ecosystem balance. In contrast, soil microbiomes present a promising avenue for sustainable agriculture, offering the potential to increase crop yields, enhance nutrient use efficiency, bolster plant resistance to environmental stresses, and improve overall plant health. Recent innovations in this field focus on leveraging soil microbiomes through novel strategies, such as applying microbial inoculants—composed mainly of bacteria and fungi—to achieve bioremediation, improve soil quality and fertility, and even replace traditional inorganic fertilizers. This approach also extends to biocontrol measures for pest and disease management, significantly reducing the reliance on chemical inputs. Furthermore, cutting-edge developments include cognitive biofertilizers, the optimization of crop variants tailored to seasonal and geographical conditions, and the selection of crop species and genotypes with increased resilience. These advancements mark a significant shift towards more sustainable agricultural practices by harnessing the inherent capabilities of soil microbiomes to restore soil health, enhance nutrient cycling, and support long-term crop productivity. This integrated approach represents a critical innovation in the quest for sustainable food production systems, offering a holistic alternative to conventional, chemically intensive methods. Graphical Abstract